Senior High School Students’ Difficulties in Comprehending Report Text - Khaerunnisa Khaerunnisa; Chairil Anwar Korompot; Fauzan Hari Sudding Sally (Journal of Excellence in English Language Education, 2026)
This study aims to find out the difficulties of grade X students in comprehending report text and the factors it. This study used a mixed method through tests and interviews as research instruments. The results showed that there were 46.67% of students had difficulty in making inference, 43.34% of students had difficulty in identifying references, 42.50% of students had difficulty in determining the main idea, 41.67% of students had difficulty in understanding vocabulary, and 39.33% of students had difficulty in detailing information. Then there are six factors that cause students to have difficulty in comprehending report text. They are, limited vocabulary knowledge, lack of fluency, inadequate use of effective reading strategies, problems with information processing, and low reading interest and motivation. This study suggests that teachers focus their attention on developing and implementing effective learning solutions to improve students' understanding of report texts.